2004
DOI: 10.1136/jcp.2004.018648
|View full text |Cite
|
Sign up to set email alerts
|

Cost efficiency analysis of modern cytocentrifugation methods versus liquid based (Cytyc Thinprep®) processing of urinary samples

Abstract: Background/Aims: Liquid based cytology (LBC) was developed as a replacement for cytocentrifugation in the treatment of cell suspensions. Because accurate data comparing the quality and total cost of modern cytocentrifugation methods versus LBC in non-gynaecological samples are not available, this study was designed to investigate these issues. Methods: The study comprised 224 urine samples treated with the Thermo Shandon CytospinH 4 using reusable TPXH chambers, disposable CytofunnelsH for samples up to 0.5 ml… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
45
0
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(47 citation statements)
references
References 13 publications
1
45
0
1
Order By: Relevance
“…13 Since the early 1990s, after the onset of marketing of ThinPrep for use in evaluating nongynecological specimens, there have been many studies comparing ThinPrep with more conventional processing techniques (e.g., cytocentrifugation, direct smear, filtration) for urine cytology. [4][5][6][7][8][9][10] These studies have produced conflicting conclusions. Elsheikh et al 5 preferred ThinPrep over conventional CS in the majority of nongynecologic, including urinary cytology cases.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…13 Since the early 1990s, after the onset of marketing of ThinPrep for use in evaluating nongynecological specimens, there have been many studies comparing ThinPrep with more conventional processing techniques (e.g., cytocentrifugation, direct smear, filtration) for urine cytology. [4][5][6][7][8][9][10] These studies have produced conflicting conclusions. Elsheikh et al 5 preferred ThinPrep over conventional CS in the majority of nongynecologic, including urinary cytology cases.…”
Section: Discussionmentioning
confidence: 99%
“…However, other studies have concluded that conventional methods, such as cytocentrifugation, are more appropriate HIGH-GRADE UROTHELIAL CARCINOMA Diagnostic Cytopathology, Vol 37, No 1 than ThinPrep for the treatment of urine cytology samples and that in cases of malignancy, CS is superior in terms of interpreting the cytomorphologic details. 4,7,8 There have been only a few documented reports comparing SP with conventional preparations for the evaluation of urine cytology specimens. 9,11,12 These studies have shown mixed results.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the urine, the use of the Thinprep s 2000 (Cytyc Corp., Boxborough, MA, USA) processor results in increased cellularity and marked reduction of debris, erythrocytes and crystals (Anagnostopoulou et al, 2000;Wright and Halford 2001;Piaton et al, 2002Piaton et al, , 2004. Additionally, complementary techniques such as immunocytochemistry, DNA, RNA and protein molecular analysis can be successfully applied to Thinprep sprocessed samples, thus allowing the impact of biomarkers in a variety of human malignancies to be studied (Tisserand et al, 2003).…”
mentioning
confidence: 99%
“…3,4 Therefore, urinary cytology is another important approach for making the diagnosis and follow-up of bladder cancer. This procedure is noninvasive and quite sensitive for high grade urothelial lesions irrespective of their location in the urinary tract.…”
Section: Introductionmentioning
confidence: 99%